Some Properties of the p-Adic Beta Function (European Journal of Pure and Applied Mathematics, 2015)
In the present work we define a $p$-adic analogue of the classicalbeta function by using Y. Morita's $p$-adic gamma function. Weobtain some elementary properties of the $p$-adic beta function. Wegive some relations between the classical beta and the $p$-adic betafunctions at the values of natural numbers.